Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F; Olesen, Arne V; Forsberg, René; Casal, Tania G (Journal of Geophysical Research: Earth Surface, 2019)
The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4,320 km2. Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; radar observasjoner; satellite bilder; subglasial innsjø; topografi

Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

Vil isen i Antarktis smelte? - Østerhus, Svein (2018)
Isen i Antarktis smelter ikkje med det første, men store endringar er undervegs i havet. Havvatnet rundt Antarktis er iskaldt, men nå observerer vi at varmare vatn strøymer innunder den flytande delen av is-kappen. Om denne utviklinga ikkje stopper vil meir innlandsis strøyme ut i havet og føre til at havnivået vil stige med fleire meter. Det er langt frå sikkert at dette vil skje, men det er eit veldig viktig klimaspørsmål som vi må forstå betre. Difor har Uni Research med støtte av Forskingsrådet og Polarinstituttet bygd fleire havobservatorium for å kunne gi eit tidleg varsel dramatisk endringar.
Publication Title: Forskning.no
Keywords: Sørishavet; havnivåstigning; issmelting; klimaendringer; populærvitenskap

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi

Antarctic ice rises: small in size but big on impact - Matsuoka, Kenichi (Fram forum, 2017)
Ice discharge from the Antarctic Ice Sheet directly impacts global sea level, making ice sheet dynamics a central topic in antarctic research. Glaciologists are studying a poorly understood but potentially important phenomenon that looks like a little hill of ice. They call these hills “ice rises”.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf

A constitutive framework for predicting weakening and reduced buttressing of ice shelves based on observations of the progressive deterioration of the remnant Larsen B Ice Shelf - Borstad, Chris; Khazendar, Ala; Scheuchl, Bernd; Morlighem, Mathieu; Larour, Eric; Rignot, Eric (Geophysical Research Letters, 2016)
The increasing contribution of the Antarctic Ice Sheet to sea level rise is linked to reductions in ice shelf buttressing, driven in large part by basal melting of ice shelves. These ocean-driven buttressing losses are being compounded as ice shelves weaken and fracture. To date, model projections of ice sheet evolution have not accounted for weakening ice shelves. Here we present the first constitutive framework for ice deformation that explicitly includes mechanical weakening, based on observations of the progressive degradation of the remnant Larsen B Ice Shelf from 2000 to 2015. We implement this framework in an ice sheet model and are able to reproduce most of the observed weakening of the ice shelf. In addition to predicting ice shelf weakening and reduced buttressing, this new framework opens the door for improved understanding and predictions of iceberg calving, meltwater routing and hydrofracture, and ice shelf collapse.
Keywords: Antarktis; glasiologi; global oppvarming; havnivåstigning; innlandsis; isbrem; isshelf; smelting

Investigating uncertainty in the simulation of the Antarctic ice sheet during the mid-Piacenzian - Yan, Qing; Zhang, Zhongshi; Wang, Huijun (Journal of Geophysical Research: Atmospheres, 2016)
The mid-Piacenzian (~3 Ma) represents the most recent warm period in Earth's history on a geological time scale; it is characterized by a significant rise of global sea level. The simulation of the size and location of the ice sheets and the investigation of the uncertainty in the simulations are potentially helpful for constraining reconstructed sea level changes. In this study, we focus on the behavior of the Antarctic ice sheet (AIS) in the mid-Piacenzian. We investigate the influence of topography correction, model parameters, climate forcings, and model resolution on the modeled AIS and explore the isolated role of atmospheric and oceanic forcings. Forced by the simulated climate changes with the Norwegian Earth System Model, the Parallel Ice Sheet Model (15 km × 15 km) produces a nearly collapsed West AIS (WAIS) in the mid-Piacenzian, with no significant retreat of the East AIS (EAIS). The role of increased air temperature plays a key role in the mass loss of the mid-Piacenzian AIS, while its role is comparable to the role of ocean warming on the melting of the WAIS. In terms of the range of sea level changes, the largest source of uncertainty in the modeled AIS is derived from ice sheet model parameters and climate forcings. Although the employed model parameters, topography correction factors, and model resolution affect the simulated AIS in the mid-Piacenzian, large-scale deglaciation of the EAIS in our sensitivity experiments may only be possible with additional warming.
Keywords: Antarktis; atmosfæren; geologi; havnivåstigning; innlandsis; klimaendringer; paleontologi

Antarktis: inlandsis, shelf-is och stigande havsnivå - Darelius, Elin (Naturen, 2014)
I klimatsammanhang har strålkastarljuset länge varit riktade mot de känsliga polarområdena och smältande is. Bilder på isbjörnar som klamrar sig fast vid ett ensamt isflak figurerar varje höst i media när årets – ofta rekordlåga – minimum i utbredning av Arktisk havsis offentliggörs. Men nyligen har is-överskrifterna allt oftare kommit söderifrån, de har handlat om Antarktis, om shelf-is som smälter, om en stigande havsnivå och om möjligheten för att inlandsisen i Väst-Antarktis ska kollapsa.
Keywords: Sørishavet; brehylle; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Recent snowfall anomalies in Dronning Maud Land, East Antarctica, in a historical and future climate perspective - Lenaerts, Jan T M; van Meijgaard, Erik; van den Broeke, Michiel R; Ligtenberg, Stefan R M; Horwath, Martin; Isaksson, Elisabeth (Geophysical Research Letters, 2013)
Enhanced snowfall on the East Antarctic ice sheet is projected to significantly mitigate 21st century global sea level rise. In recent years (2009 and 2011), regionally extreme snowfall anomalies in Dronning Maud Land, in the Atlantic sector of East Antarctica, have been observed. It has been unclear, however, whether these anomalies can be ascribed to natural decadal variability, or whether they could signal the beginning of a long-term increase of snowfall. Here we use output of a regional atmospheric climate model, evaluated with available firn core records and gravimetry observations, and show that such episodes had not been seen previously in the satellite climate data era (1979). Comparisons with historical data that originate from firn cores, one with records extending back to the 18th century, confirm that accumulation anomalies of this scale have not occurred in the past ~60 years, although comparable anomalies are found further back in time. We examined several regional climate model projections, describing various warming scenarios into the 21st century. Anomalies with magnitudes similar to the recently observed ones were not present in the model output for the current climate, but were found increasingly probable toward the end of the 21st century.
Keywords: Dronning Maud Land; glasiologi; global oppvarming; havnivåstigning; innlandsis; klimaendringer; klimatologi

Surface mass balance on Fimbul ice shelf, East Antarctica: Comparison of field measurements and large-scale studies - Sinisalo, Anna; Anschütz, Helgard; Aasen, Anne Tårånd; Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Matsuoka, Kenichi; Hamran, Svein- Erik; Øyan, Mats-Jørgen; Schlosser, Elisabeth; Hagen, Jon Ove; Nøst, Ole Anders; et al. (Journal of Geophysical Research: Atmospheres, 2013)
Many challenges remain for estimating the Antarctic ice sheet surface mass balance (SMB), which represents a major uncertainty in predictions of future sea-level rise. Validating continental scale studies is hampered by the sparse distribution of in situ data. Here we present a 26 year mean SMB of the Fimbul ice shelf in East Antarctica between 1983–2009, and recent interannual variability since 2010. We compare these data to the results of large-scale SMB studies for similar time periods, obtained from regional atmospheric modeling and remote sensing. Our in situ data include ground penetrating radar, firn cores, and mass balance stakes and provide information on both temporal and spatial scales. The 26 year mean SMB on the Fimbul ice shelf varies between 170 and 620 kg m−2 a−1 giving a regional average value of 310 ± 70 kg m−2 a−1. Our measurements indicate higher long-term accumulation over large parts of the ice shelf compared to the large-scale studies. We also show that the variability of the mean annual SMB, which can be up to 90%, can be a dominant factor in short-term estimates. The results emphasize the importance of using a combination of ground-based validation data, regional climate models, and remote sensing over a relevant time period in order to achieve a reliable SMB for Antarctica.
Keywords: Dronning Maud Land; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Svarene på fortidens klimavariasjoner og framtidens havnivå ligger begravd i isen i Antarktis - Winther, Jan-Gunnar; Isaksson, Elisabeth (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Det Internasjonale polaråret 2007; Dronning Maud Land; glasiologi; havnivåstigning; klimaendringer; polarforskning

An extreme precipitation event in Dronning Maud Land, Antarctica: a case study with the Antarctic Mesoscale Prediction System - Schlosser, Elisabeth; Powers, Jordan G.; Duda, Michael G.; Manning, Kevin W.; Reijmer, Carleen H.; van den Broeke, Michiel R. (Polar Research, 2010)
An extreme precipitation event that influenced almost the whole polar plateau of Dronning Maud Land, Antarctica, is investigated using Antarctic Mesoscale Prediction System archive data. For the first time a high-resolution atmospheric model especially adapted for polar regions was used for such a study in Dronning Maud Land. The outstanding event of 21–25 February 2003 was connected to a strong north-westerly flow, caused by a blocking high above eastern Dronning Maud Land, that persisted for several days and brought unusually large levels of moisture to the Antarctic Plateau. This weather situation is most effective in bringing precipitation to high-altitude interior Antarctic ice-core drilling sites, where precipitation in the form of diamond dust usually dominates. However, a few such precipitation events per year can account for a large percentage of the annual accumulation, which can cause a strong bias in ice-core data. Additionally, increased temperatures and wind speeds during these events need to be taken into account for the correct climatic interpretation of ice cores. A better understanding of the frequency of occurrence of intermittent precipitation in the interior of Antarctica in past and future climates is necessary for both palaeoclimatological studies and estimates of future sea-level change.
Keywords: Dronning Maud Land; havnivåstigning; klimaendringer; klimatologi; meteorologi; nedbør; polarområdene